Strengthening Village SDGs-Based Development Program Implementation in Blora to Support The 2045 Golden Indonesia Vision - Ngabiyanto; Munandar, Moh Aris; Lestari, Puji; Rahman, Yozi Aulia; Fauzi, Ahmad Syahrul (Universitas Negeri Semarang, 2025)
Indonesia has established the Vision of Golden Indonesia 2045 in the National Long-Term Development Plan (RPJPN) 2025–2045 with the goal of becoming a developed country and escaping the middle-income trap. The achievement of this vision greatly depends on the successful implementation of the Sustainable Development Goals (SDGs). As part of the effort to localize the SDGs, the Village SDGs (SDGs Desa) were formulated, focusing on 18 development goals at the village level. One region with a still low Village SDGs score is Blora Regency, which recorded a score of 46.20 in 2022. In response to this issue, this community service activity was carried out in collaboration with one of the villages in Blora, namely Gadu Village, Sambong Subdistrict, Blora Regency. This activity was conducted through socialization on the preparation of village development programs based on the SDGs, as well as assistance in village development planning referring to SDGs indicators in accordance with national regulations. Through this community service activity, it is expected that the community and village officials will be able to design strategic programs to accelerate the achievement of the Village SDGs while also supporting the realization of the national vision of Golden Indonesia 2045. This activity had a positive impact on the development planning process in Gadu Village. The results showed several development programs in Gadu Village identified as potentially accelerating Village SDGs achievement and supporting the realization of the Golden Indonesia 2045 vision.